2009
DOI: 10.1186/1744-9081-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Coincident frequencies and relative phases among brain activity and hormonal signals

Abstract: Background: Fourier transform is a basic tool for analyzing biological signals and is computed for a finite sequence of data sample. The electroencephalographic (EEG) signals analyzed with this method provide only information based on the frequency range, for short periods. In some cases, for long periods it can be useful to know whether EEG signals coincide or have a relative phase between them or with other biological signals. Some studies have evidenced that sex hormones and EEG signals show oscillations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The previously described outcome (Solís-Ortiz, Campos, Felix, & Obregón, 2009) indicated that the estrogen levels of participants displayed significantly change over the menstrual cycle (X 2 (9) = 74.08, p = 0.001). Comparisons post hoc demonstrated that estrogen levels were higher during the days 14 of the menstrual cycle (t = −34.29, p = 0.001) compared with the day 1of menstruation, when the estrogen levels are lower.…”
Section: Hormonesmentioning
confidence: 81%
See 3 more Smart Citations
“…The previously described outcome (Solís-Ortiz, Campos, Felix, & Obregón, 2009) indicated that the estrogen levels of participants displayed significantly change over the menstrual cycle (X 2 (9) = 74.08, p = 0.001). Comparisons post hoc demonstrated that estrogen levels were higher during the days 14 of the menstrual cycle (t = −34.29, p = 0.001) compared with the day 1of menstruation, when the estrogen levels are lower.…”
Section: Hormonesmentioning
confidence: 81%
“…The current study also employed a dataset of estrogen and progesterone levels in serum obtained before starting the sessions of EEG across of the menstrual cycle previously reported (Solís-Ortiz, Campos, Felix, & Obregón, 2009;Solís-Ortiz & Corsi-Cabrera, 2002). The serum hormone levels were employed to confirm the hormone levels during the menstrual cycle and to establish relations with EEG frequencies and anxiety frequencies.…”
Section: Hormonesmentioning
confidence: 99%
See 2 more Smart Citations
“…En reposo, durante la fase periovulatoria, existe un incremento de la correlación interfrontal y un decremento de la PA. En contraste, en la fase menstrual, se incrementa la PA de las frecuencias rápidas, mientras que la PR de theta decrece [24]. Además, en las mujeres existe una correlación positiva entre los niveles de progesterona y la PA de las bandas theta, alfa1, alfa2 y beta1, así como una correlación negativa con las bandas delta y beta2 [25].…”
Section: Efecto Del Alcohol En La Organización Eléctrica Cerebral Durunclassified